Radiation therapists' compliance to a palliative imaging protocol: a case report. Issue 2 (8th January 2018) - Cvetkova, J.; O'Donovan, T.; Craig, A.; Mullaney, L.
Abstract: Background: Imaging protocols are implemented to identify and minimise set-up errors. A crucial component to the success of these protocols is staff compliance. Materials and methods: This is case report describing a retrospective review of radiation therapists' compliance to a palliative imaging protocol in a single large institution in one calendar year. Results: The review showed a non-compliance to protocol for 8% of treatments. The most frequent protocol deviation was a failure to calculate the mean set-up displacement after 2/3 days of consecutive imaging. Conclusion: Despite the presence of institutional evidence-based palliative imaging protocol unwanted deviations in practice can occur.